Estudo da relação de ordem-desordem estrutural em nanopartículas de TiO2 - Silva Junior, Eurípedes [UNESP] (2015)
In this work, TiO2 nanoparticles were obtained from methodology based on the sol-gel process followed by the microwave-assisted solvothermal method (MAS), in different processing times. The TiO2 were characterized by thermal analysis (TG/DSC), X-ray Diffraction (XRD), Raman spectroscopy, electron paramagnetic resonance (EPR), high-resolution transmission electron microscopy (HR-TEM), energy dispersive spectroscopy (EDS), X-ray Photoelectron spectroscopy (XPS). Porosity and surface analysis were performed from the Brunauer-Emmett-Teller (BET) method, while the optical properties were investigated by UV-Vis absorption spectroscopy, photoluminescence (PL) and photocatalytic experiments. The calcination temperatures at 380 °C and 450 °C were responsible by the heterostructured (anatase + bruquita) and the monophase (anatase) crystalline materials, respectively. However, at short range are highly ordered due the presence of vibrational modes ascribed to only anatase phase active in Raman. The FEG-SEM e HR-TEM results showed TiO2is a polycrystalline material consisting of nanocrystals (~10 nm) grow up by means of the Oriented attachment mechanism, resulting in a microscopic agglomeration of nanoparticles. The presence of structural defects was attributed to singly ionized oxygen vacancies (VO•) by EPR signals at g≈2,023 and g≈1,966, which according to XPS and EDS results, suggest that these vacancies are in both bulk and surface. From the Rietveld refinement, the oxygen vacancies were interpreted as deviations from (Ti−O) and (O−T̂i−O), which tend to turn the ordered [TiO6] clusters in complex clusters [TiO5.VOx], [TiO5.VO•] and [TiO5.VO••]. The decreasing in the optical band gap (2,68-2,99 eV) and the PL at room temperature, indicate that these complex clusters represent the defects responsible for disorder at medium-range which exhibit a broadband at visible (350-700 nm) and another...